2022
DOI: 10.25130/tjas.22.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting in Some Productive Traits for Local and Turkish Awassi Sheep

Abstract: The aim of study effecting fixed factors (breed, year of birth, age of dam, sex of lambs) in total milk yield and milk composition and some of growth traits (birth weight and weaning weight), the overall mean of milk yield (66.58 ±1.67. kg) ,it was breed effect significant (P<0.05) , while the effect factors (birth year, age of the ewe, sex of lambs, type of birth) was not significant, , the overall mean of milk components (fat, lactose, protein, non-fat solids) was 4.18 ± 0.29, 4.42 ± 0.02, 5.47 ± 0.11 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The current study did not record a significant effect of the breed on the weight of lambs at birth, as it recorded averages of 3.87 , 3.88 , 3.85 kg, respectively, for Awassi and Kreishi lambs and their mixtures (Table ,1), and this result came close to the results of [10], in his study on Awassi sheep and confirmed the results [11] in their study of three breed of sheep, the local and Turkish Awassi sheep, and their crosses. Contrary to the results of Ahmed and others (2015) in their study of four breeds of sheep, which are the local Awassi, the Turkish, the Kurdish and the Hamdaniya sheep, and [12], who noticed significant differences between the breed in the weight of lambs at birth.…”
Section: Effect Of Breed On Lambs Birth Weight and Body Measurementssupporting
confidence: 91%
“…The current study did not record a significant effect of the breed on the weight of lambs at birth, as it recorded averages of 3.87 , 3.88 , 3.85 kg, respectively, for Awassi and Kreishi lambs and their mixtures (Table ,1), and this result came close to the results of [10], in his study on Awassi sheep and confirmed the results [11] in their study of three breed of sheep, the local and Turkish Awassi sheep, and their crosses. Contrary to the results of Ahmed and others (2015) in their study of four breeds of sheep, which are the local Awassi, the Turkish, the Kurdish and the Hamdaniya sheep, and [12], who noticed significant differences between the breed in the weight of lambs at birth.…”
Section: Effect Of Breed On Lambs Birth Weight and Body Measurementssupporting
confidence: 91%
“…Table (1) indicates the average of the important studied traits on Al-Arabi sheep in southern Iraq, as well as the value of the standard deviation for each trait, with a statement of the lowest and highest values for each trait to clarify the extent to which these traits appeared in this study ,We may notice a high range between the highest and lowest reading due to the difference of the experimental animals in terms of age and gender, which are the two factors that were entered into the mathematical model of the experiment to reduce the experimental error. Through the results of the correlation coefficient of the economically important traits in this study (Table 2), we note that the hot carcass weight was significantly (P≤0.01) and positively correlated with each of the traits of carcass length and diameter and thigh weight at varying rates (0.63, 0.36 and 0.59).respectively While the correlations of hot carcass weight with each of the dressing percentage and fiber breakage index were negative and not significant, and it was positive and insignificant with each of the pH of meat, water holding capacity in the muscle and the diameter of the muscle fiber.…”
Section: Resultsmentioning
confidence: 99%
“…The Iraqi sheep are of the genus of Asian sheep with a broad mechanism and include three breeds: Awassi, Arabi and Karadi, whose numbers have decreased from what it was in the past few years, due to the unstable conditions in which Iraq lived (FAO, 2019), It is raised and lives on the margins of agriculture and natural pastures and feeds on what is left behind in the cultivated lands, so its production and fertility are low, which requires promoting and developing the means of breeding and developing them using scientific to the deterioration and lack of natural pastures, drought and the spread of diseases, or due to heat stress resulting from high temperatures, as well as the difficulty of using means of genetic and physiological improvement and modern technologies. Which led to a decline in their performance (Ishaq and Ajil, 2013). In recent years, significant progress has been made in sheep breeding, but it is too slow to improve the quality of production performance before genetics and molecular markers applications become an accessible technology with wide applications that increase the accuracy and quantity of genetic improvement in breeding methods (Gao et al, 2007and Pareek et al, 2011and Jaayid, 2013.Softness, juiciness and flavor are among the qualitative traits that affect consumer acceptance of meat and its products, and it is one of the most important qualities that make meat more palatable.…”
Section: Introcuctionmentioning
confidence: 99%